2008
DOI: 10.1182/blood-2008-01-136713
|View full text |Cite
|
Sign up to set email alerts
|

Long-term expansion of effector/memory Vδ2− γδ T cells is a specific blood signature of CMV infection

Abstract: The ability of human ␥␦ T cells to develop immunologic memory is still a matter of debate. We previously demonstrated the involvement of V␦2 ؊ ␥␦ T lymphocytes in the response of immunosuppressed organ recipients to cytomegalovirus (CMV). Here, we demonstrate their ability to mount an adaptive immune response to CMV in immunocompetent subjects. V␦2 ؊ ␥␦ T-cell peripheral blood numbers, repertoire restriction, and cytotoxicity against CMV-infected fibroblasts were markedly increased in CMV-seropositive, compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
226
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(268 citation statements)
references
References 43 publications
28
226
1
1
Order By: Relevance
“…11) in SOTR [128][129][130] and in immune-competent subjects [131] as well as in foetuses with congenital infection [132]. This expansion has been interpreted as a type of specific signature of the adaptive immune response to HCMV infection [133]. Following expansion, g/d T cells were found to be able to kill HCMV-infected target cells in vitro [134], and CD16 (FcgRIIIA) was found to be specifically expressed by the majority of HCMV-induced g/d T cells.…”
Section: Innate and Adaptive T Cell Immunity To Hcmv And The Pcmentioning
confidence: 99%
“…11) in SOTR [128][129][130] and in immune-competent subjects [131] as well as in foetuses with congenital infection [132]. This expansion has been interpreted as a type of specific signature of the adaptive immune response to HCMV infection [133]. Following expansion, g/d T cells were found to be able to kill HCMV-infected target cells in vitro [134], and CD16 (FcgRIIIA) was found to be specifically expressed by the majority of HCMV-induced g/d T cells.…”
Section: Innate and Adaptive T Cell Immunity To Hcmv And The Pcmentioning
confidence: 99%
“…After CMV infection, but not after other viral infections (e.g. herpes simplex virus, Varicella zoster virus, Epstein-Barr virus and influenza), Vd2 neg cd T cells undergo massive expansion in the blood of kidney transplant recipients (KTRs) (14,17). Recently, we demonstrated that Vd2 neg cd T cell expansion in the peripheral blood of KTRs was associated with the resolution of infection, and we observed a higher risk of recurrence at the end of a curative treatment in the absence of Vd2 neg cd T cell expansion (18).…”
Section: Introductionmentioning
confidence: 99%
“…Primary gd T-cell lines (Vd1, Vd1C3, Vd5) and Vd2 neg gd T-cell clones (Vg8Vd3, Vg2Vd3) were generated and cultured following the same methods as described previously. 14,35 For co-culture functional assays and IFNg secretion, primary T-cell lines and clones (5 £ 10 4 cells per well) were incubated with monolayers of tumor cell lines or HUVECs that were uninfected or infected with the human CMV clinical strain TB40-E as described. 35 After 24 h at 37 C, supernatants were isolated by centrifugation, and cytokine secretion (IFNg and TNFa) was measured by ELISA.…”
Section: Methodsmentioning
confidence: 99%
“…11 Interestingly, AICD seems to be reduced for epithelial Vd2 neg gd T cells, and increasing evidence supports an important role of this subset for tumor and infection immunosurveillance. 12 Human Vd2 neg gd T cells expand in the periphery of individuals during CMV infection in various pathophysiological contexts, including solid-organ and stem cell transplantation, [13][14][15][16][17] where they develop cytotoxic function and produce proinflammatory cytokines such as tumor necrosis factor a (TNFa) and IFNg. 18 Importantly, CMV-induced expansion of Vd2 neg gd T cells correlates with decreased susceptibility to post-transplant cancers, suggesting a role in tumor immunosurveillance in vivo.…”
Section: Introductionmentioning
confidence: 99%